Frustration tolerance, self-esteem, academic achievement and sociocultural variables an exploratory study on U.P. Diliman students - Bolaños, Melissa D. (2008)
The triadic constructs: frustration tolerance, self-esteem, and academic achievement functioned as major conceptual templates in the study. This study intended to unlock the interconnection of the constructs and the influence of the sociocultural variables of each construct. It aimed to present a holistic description of UP students' predispositions in the academe. Two quantitative research designs, correlation and causal comparative, were adopted. 734 undergraduate students from the University of the Philippines from 18 of its colleges were congregated to participate in the study. Frustration Discomfort Scale was used to appraise frustration tolerance and the Rosenberg Self-esteem Scale to assess self-esteem. It can be concluded that UP students who partook in the study embodied an almost homogeneous psychological functioning despite diverse orientations.They displayed minimal variations in terms of psychological functioning.